Wrinkled titanium nitride nanocomposite for robust bendable electrodes. (23rd September 2019) - Gence, L; Escalona, M; Castillo, C; Quero, F; Saikia, P; Wheatley, R; Diaz-Droguett, D E; Retamal, M J; Volkmann, U G; Bhuyan, H
Abstract: Electrical contacts and interconnections are critical components for all electronic devices. Bendable electrodes with enhanced electro-mechanical properties are highly desirable to develop innovative wearable electronic devices. Herein we report on a fabrication method for robust bendable coatings based on titanium nitride (TiN) thin films and silver nanowires (Ag NWs). TiN and TiN-AgNWs nanocomposites were deposited on polyethylene terephthalate (PET) substrates using a plasma enhanced pulsed laser deposition (PLD) technique. The resulting TiN coatings exhibit excellent adhesion to PET and their sheet resistance can be tuned using a dual frequency PLD process and further decreased by incorporating Ag NWs into the TiN layers. Sample sheet resistance was decreased down to values as low as R S = 3.5 Ω / □ corresponding to the formation of TiN-AgNWs nanocomposites. The electro-mechanical robustness of TiN based coatings were evaluated by four-probe resistance measurements in situ under cyclic bending tests. We show that the TiNAgNWs nanocomposites surpass both ITO and Ag NWs coatings in terms of mechanical robustness and electrical conductivity respectively. These nanocomposites withstand high strain fatigue loading up to ϵ  = 2.6%, keeping R S below 5 Ω/□. The data demonstrates that the incorporation of Ag NWs in TiN coatings improve the mechanical robustness, limiting the crack growth and propagation, with low optical transmittance decrease (≈11%). These results indicate that Ag NWs based nanocomposites are attractive materials for flexible electronic devices.